Bridging Isolation or Breaking Nature? Community Perception on Road Development in a Conservation Area - Emi Roslinda; Eka Novia Mahesti; Lilis Listyawati (Green Insight Solutions, 2025)
Infrastructure development in conservation areas is a double-edged sword, offering potential socio-economic benefits while posing environmental risks. This study examines community perceptions of the construction of a parallel road in Tanjung Lokang Village, located within the Betung Kerihun National Park, Indonesia. The research utilized a survey method involving 65 households across two hamlets, Tanjung Lokang and Bu’ung, through interviews and observations. Data were analyzed using descriptive qualitative techniques. The results revealed that community perceptions vary across social, economic, and environmental aspects. Socially, most residents in Tanjung Lokang view the road positively, citing improved mobility, technology access, education, and healthcare. However, respondents in Bu’ung Hamlet expressed less enthusiasm due to limited physical access to the road. Economically, both hamlets anticipated significant benefits, including increased income, market access, and business opportunities. In contrast, environmental perceptions were mixed. While some community members acknowledged the road’s potential to support eco-tourism and environmental services, others expressed concern over forest disturbance, biodiversity loss, and deforestation due to increased land use and shifting cultivation. The findings emphasize the importance of inclusive planning and empowerment initiatives to mitigate negative environmental impacts while optimizing community welfare. A balanced development approach is crucial to align local aspirations with conservation objectives.